Gambaran Tingkat Pengetahuan Ibu tentang Tahapan Pemberian MPASI Usia 6-11 Bulan di Wilayah Kerja Puskesmas Cilongok 1 - Raihan Ayuraira Febriyoni; Wulan Margiana (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2024)
The intake from complementary feeding (MPASI) acquired by a child plays a significant role in determining the child's nutritional status. The administration of MPASI continues with breastfeeding from 6 months to 2 years. The adequacy of MPASI refers to food that can meet the nutritional needs of the child. The majority of developmental delay cases are attributed to poor-quality MPASI. The purpose of this study was to describe the level of knowledge of mothers about the stages of giving complementary feeding (MPASI) aged 6-11 months in the working area of ​​Cilongok 1 Public Health Center.This study aims to determine maternal knowledge regarding the stages of complementary feeding (MPASI) for infants aged 6-11 months in the Public Health Care Center Cilongok 1 operational area. This research was a quantitative study with a descriptive design. A total of 196 respondents were used for the sample, chosen through purposive sampling. The instrument used in this study was a questionnaire. From two respondent groups, namely the group of mothers with infants aged 6-8 months, 70 (59%) had good knowledge, 37 (31%) had sufficient knowledge, and 12 (10%) had inadequate knowledge. For the group of mothers with infants aged 9-11 months, 35 (46%) had good knowledge, 24 (31%) had sufficient knowledge, and 18 (23%) had inadequate knowledge. The description of maternal knowledge concerning MPASI for infants aged 6-11 months in the operational area of the Puskesmas Cilongok 1 is deemed satisfactory.